Multiplex Network Ties and the Spatial Diffusion of Radical Innovations: Martin Luther’s Leadership in the Early Reformation - Becker, Sascha O.; Hsiao, Yuan; Pfaff, Steven; Rubin, Jared (American Sociological Review, 2020)
This article analyzes Martin Luther’s role in spreading the early Reformation, one of the most important episodes of radical institutional change in the last millennium. We argue that social relations played a key role in its diffusion because the spread of heterodox ideologies and their eventual institutionalization relied not only on private “infection” through exposure to innovation but also on active conversion and promotion of that new faith through personal ties. We conceive of that process as leader-to-follower directional influence originating with Luther and flowing to local elites through personal ties. Based on novel data on Luther’s correspondence, Luther’s visits, and student enrollments in Luther’s city of Wittenberg, we reconstruct Luther’s influence network to examine whether local connections to him increased the odds of adopting Protestantism. Using regression analyses and simulations based on empirical network data, we find that the combination of personal/relational diffusion via Luther’s multiplex ties and spatial/structural diffusion via trade routes fostered cities’ adoption of the Reformation, making possible Protestantism’s early breakthrough from a regional movement to a general rebellion against the Roman Catholic Church.